2013
DOI: 10.1017/s0022149x13000588
|View full text |Cite
|
Sign up to set email alerts
|

ATaenia crassicepsmetacestode factor enhances ovarian follicle atresia and oocyte degeneration in female mice

Abstract: The histopathological effects of Taenia crassiceps infection or T. crassiceps metacestode factor inoculation on the mouse ovary were determined using six female mice in three groups: infected mice, mice inoculated with the metacestode factor and control mice. The control group was subcutaneously inoculated with healthy peritoneal fluid. The infected group was intraperitoneally inoculated with 40 T. crassiceps metacestodes, and the metacestode factor group was subcutaneously inoculated with T. crassiceps metace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…In addition to the histopathological changes in the murine spleen that were observed here, we have previously reported that the T. crassiceps MF leads to the disruption and apoptosis of seminiferous epithelium cells in male mice (Zepeda et al, 2011b), which are similar to those induced by a T. crassiceps metacestode infection in male mice (Zepeda et al, 2011a), and to a significant increase in follicular atresia and oocyte degeneration in the ovaries of female mice, which are similar to the effects caused by a T. crassiceps metacestode infection in female mice (Solano et al, 2015). Other studies have reported that T. crassiceps infection does not kill the host and can cause chronic infections with minimal damage in mice, inducing an initial Th1 response replaced by Th2 and a change in macrophage phenotype from a CAM population to an AAM population (Peó n et al, 2013).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In addition to the histopathological changes in the murine spleen that were observed here, we have previously reported that the T. crassiceps MF leads to the disruption and apoptosis of seminiferous epithelium cells in male mice (Zepeda et al, 2011b), which are similar to those induced by a T. crassiceps metacestode infection in male mice (Zepeda et al, 2011a), and to a significant increase in follicular atresia and oocyte degeneration in the ovaries of female mice, which are similar to the effects caused by a T. crassiceps metacestode infection in female mice (Solano et al, 2015). Other studies have reported that T. crassiceps infection does not kill the host and can cause chronic infections with minimal damage in mice, inducing an initial Th1 response replaced by Th2 and a change in macrophage phenotype from a CAM population to an AAM population (Peó n et al, 2013).…”
Section: Discussionsupporting
confidence: 78%
“…Other studies have reported that T. crassiceps metacestode excretion/secretion products suppress T-cell proliferative responses in vitro and IFN-g and IL-4 production in the early stages of infection (Spolski et al, 2000). Recently, the T. crassiceps MF was reported to induce structural damage in somatic and germinative cells of male mouse testes and to significantly increase atresia of primary and secondary ovary follicles in female mice (Zepeda et al, 2011b;Solano et al, 2015).…”
Section: Introductionmentioning
confidence: 96%
“…By preliminary NMR and infrared studies, these Sephadex G-50 fractions contain at least three aromatic components, carbohydrates such as glucose, and can induce a specific antibody response in rabbits and mice, which indicate that this factor is produced by the parasite (data not published). The non-specific way this Fac induces apoptosis in different types of cells, such as testis cells (Zepeda et al , 2011), ovary cells (Solano et al , 2015), spleen cells (Zepeda et al , 2016), and hippocampal cells (Zepeda et al ., 2017) is unknown. The learning deficit and the extensive apoptosis of hippocampal cells of experimental mice indicate a close relationship between both structure and function.…”
Section: Discussionmentioning
confidence: 99%
“…It is protein-free but contains an oligosaccharide containing glucose among other carbohydrates, and it is able to induce a specific antibody response in rabbits and in mice, which suggests that this factor is produced by the parasite (data not published); its entire structure is currently under study. When T. crassiceps MF is inoculated subcutaneously in male mice, it induces apoptosis of seminiferous tubule cells (Zepeda et al ., 20011b), while in female mice, it significantly increases ovarian follicle atresia (Solano et al ., 2015). Additionally, it induces apoptosis of lymphocytes of white and red pulps from the mouse spleen and significantly decreases splenic CD4+ T cells (Zepeda et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the psychopathology observed in human neurocysticercosis must have an organic basis, which might be induced by a low molecular weight fraction secreted by the parasite in its vesicular stage during the infection; thereafter, this fraction may migrate and damage cells in several tissues. Previously it has been reported that both T. crassiceps infection and a low molecular weight fraction (metacestode factor (MF)) isolated from secretions of T. crassiceps metacestodes induced severe histopathological damage, mainly extensive apoptosis, in mouse testis, ovary and spleen cells (Zepeda et al ., 2011a, b, 2015; Solano et al ., 2015). However, given that human neurocysticercosis appears to be associated with cognitive deficits, including memory impairments, studies that investigate the involvement of memory-related areas in neurocysticercosis are needed.…”
Section: Introductionmentioning
confidence: 99%